Pengembangan Media Pembelajaran Interaktif Materi Sistem Pernapasan Pada Manusia Untuk Sekolah Dasar - Prasetya, Aris; Ulfa, Saida; Susilaningsih, Susilaningsih (Universitas Negeri Malang, 2022)
This research and development aims to produce a product in the form of Interactive Learning Media (ILM) on the material of the human respiratory system. Research and development is a research method used to produce products. The product development method used refers to the 4D model that has been adjusted by needs (define, design, development, disseminate). However, in the field application, it is only up to the development stage due to time constraints and it is still in a pandemic condition where face-to-face learning is not recommended. In its application, ILM is a complement to learning material for the respiratory system in humans, media as a complement means that the media is applied to complement the material received by students in the classroom. The results of the product feasibility test that have been tested on media experts, material experts and students get a positive and feasible response. Based on the results that have been obtained, ILM about the respiratory system in humans is suitable for use as a learning medium in the classroom, with the ILM providing convenience in learning, stimulating students to learn, producing unique and attractive products for students.AbstrakPenelitian dan pengembangan ini bertujuan untuk menghasilkan produk berupa Media Pembelajaran Interaktif (MPI) pada materi sistem pernapasan manusia. Penelitian dan pengembangan merupakan metode penelitian yang digunakan untuk menghasilkan produk. Metode pengembangan produk yang dipakai mengacu pada model 4D yang telah disesuaikan oleh kebutuhan (define, design, development, disseminate). Namun pada penerapan di lapangan, hanya sampai tahap development disebabkan keterbatasan waktu dan masih dalam kondisi pandemi yang tidak disarankan untuk melakukan pembelajaran tatap muka. Dalam penerapannya MPI menjadi pelengkap dalam pembelajaran materi sistem pernapasan pada manusia, media sebagai pelengkap berarti media diterapkan untuk melengkapi materi yang diterima siswa di dalam kelas. Hasil dari uji kelayakan produk yang telah diujikan kepada ahli media, ahli materi dan siswa mendapatkan respon positif dan layak. Berdasarkan hasil yang telah diperoleh, MPI tentang sistem pernapasan pada manusia layak digunakan sebagai media pembelajaran di dalam kelas, dengan adanya MPI memberikan kemudahan dalam pembelajaran, menstimulus siswa untuk belajar, menghasilkan produk yang unik dan menarik terhadap siswa.